Molecularly Designed Zinc (II) Phthalocyanine Derivative as Dopant‐Free Hole‐Transporting Material of Planar Perovskite Solar Cell with Preferential Face‐on Orientation. Issue 11 (13th November 2019) - Hu, Qikun; Rezaee, Ehsan; Dong, Lei; Dong, Qingshun; Shan, Haiquan; Chen, Qian; Li, Minzhang; Cai, Siyuan; Wang, Liduo; Xu, Zong-Xiang
Abstract : Hole‐Transporting Materials In article number 1900182, Zong‐Xiang Xu and co‐workers synthesize dopant‐free hole‐transporting material containing hexamethyl‐mono‐n‐butyl‐substituted zinc phthalocyanine that demonstrates fully face‐on molecular orientation when spin‐coated on perovskite. The as‐fabricated n‐i‐p planar perovskite solar cells exhibit a high power conversion efficiency of 17.41% and long‐term stability, retaining over 90% of their initial efficiency after storage in humidity (about 75%) for 1400 h without encapsulation.